A facile approach to synthesize CdS–attapulgite as a photocatalyst for reduction reactions in water. Issue 43 (9th August 2021) - Ma, Ruixiao; Xie, Liyan; Huang, Yixuan; Zhuo, Kangji; Xu, Juan; Zhang, Yanhui
Abstract : The application of CdS–attapulgite composites in photocatalytic reduction of p -nitrophenol and Cr(vi ) demonstrated that the attapulgite could overcome the limitations of CdS. Abstract : At room temperature, a facile approach has been utilized for preparing novel CdS–attapulgite (CdS–ATP) composites and the composites were applied in photocatalytic reduction of p -nitrophenol and Cr(vi ). The effect of ATP on the photocatalytic activity of the CdS–ATP composites were studied by controlling the mass ratio of attapulgite. The results showed that the CdS–20%ATP composite has an excellent photocatalytic activity. In order to figure out the key to improve the photocatalytic efficiency, the prepared composites were characterized by Brunauer–Emmett–Teller (BET) specific surface area, UV-vis diffuse reflectance spectroscopy (DRS) and electrochemical impedance spectroscopy (EIS). The superior photocatalytic performance of the CdS–20%ATP composite can be ascribed to the existence of the ATP which can fix the CdS and prevent agglomeration. The interaction between ATP and CdS in the composites facilitates the electron transfer and also promoted their photocatalytic performance. This work provides us with some significant guidance in the development of CdS–ATP composite photocatalysts.